2013
DOI: 10.1002/ajmg.a.35896
|View full text |Cite
|
Sign up to set email alerts
|

Development of the human heart

Abstract: Molecular and genetic studies around the turn of this century have revolutionized the field of cardiac development. We now know that the primary heart tube, as seen in the early embryo contains little more than the precursors for the left ventricle, whereas the precursor cells for the remainder of the cardiac components are continuously added, to both the venous and arterial pole of the heart tube, from a single center of growth outside the heart. While the primary heart tube is growing by addition of cells, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(147 citation statements)
references
References 94 publications
1
115
0
4
Order By: Relevance
“…S1D-F, arrowheads; data not shown). Importantly, this is earlier than previously described; based exclusively on extrapolating from findings in the chicken embryonic heart, it was previously suggested that the epicardium covers the entire heart by late stage CS16 (Hirakow, 1992;Sylva et al, 2014).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…S1D-F, arrowheads; data not shown). Importantly, this is earlier than previously described; based exclusively on extrapolating from findings in the chicken embryonic heart, it was previously suggested that the epicardium covers the entire heart by late stage CS16 (Hirakow, 1992;Sylva et al, 2014).…”
Section: Resultsmentioning
confidence: 56%
“…Previous observations have suggested that epicardial growth starts by CS12 (4 weeks post-conception; equivalent to E9.5 in mouse embryos), a time point coinciding with looping of the human embryonic heart (Hirakow, 1992;Sylva et al, 2014). To further characterise the development of the embryonic epicardium, we analysed Haematoxylin and Eosin-stained serial sections of paraffin-embedded human hearts at stages CS11 to CS14 (between 4 and 5 weeks post-conception; n=3 per stage; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Su actividad en la formación del corazón es variada, contribuyendo a conformar la musculatura lisa del tracto efluyente (de salida) con su posterior división y parte del septo interventricular, además de modular la formación de los aparatos valvares aórtico y pulmonar, su inervación parasimpática y la organización de los patrones espaciales de los arcos aórticos y sus ramas colaterales (Sylva et al, 2014;Brade et al).…”
Section: Discussionunclassified
“…Original observations of professor Kurkiewicz are also cited in various textbooks and handbooks [for example 9-10, 21, 54-61] or dissertations non listed in SCI [62][63][64][65][66][67]. Furthermore, name of T. Kurkiewicz appears in numerous original publications, although his fundamental publication is not included into the references (for example "theory challenged as early as 1909 by Kurkiewicz" [68], "in 1909 Kurkiewicz identified the pro--epicardium as the source of the epicardium" [69].…”
mentioning
confidence: 99%